Local Government service delivery expectations and prospects at the Collins Chabane Local Municipality, Limpopo Province - Chauke, O. R.; Mathebula, N. E. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The Collins Chabane Local Municipality (CCLM) was established in 2016. This was after massive disruptive protests by community members predominantly from Malamulele area demanding re-demarcation and to be moved from the Thulamela Local Municipality into the new municipality (previously known as LIM345). Central to the demand of the 'new' municipality was the fact that the Thulamela Local Municipality was according to the residents failing to extend the delivery of services to the populace of the Malamulele constituents. This paper seeks to probe the expectations and prospects in relation to service delivery by the 'new' municipality. This is done through a quantitative survey questionnaire. The paper argues that inasmuch as the contention for the creation of the Collins Chabane Local Municipality was the failure of the Thulamela Local Municipality to deliver services, there is a huge expectation on the CCLM to deliver services to its constituent while also seeking to redress the 'service delivery imbalances' as claimed by the residents. The paper concludes by proposing measures on how the municipality must meet the expectations of their communities within its jurisdiction. Keywords: Demarcation, Local government, Municipality, Service delivery
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Demarcation; Local government; Municipality; Service delivery; Collins Chabane Local Municipality, Limpopop Province; Municipal services--South Africa